Prognosis Organisasi Sistem Terbuka (Studi Kasus: STIA LAN) - Drs. Awang Anwaruddin (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2004)
Organization is the arrangement of personnel for facilitating the accomplishment some agreed purpose through the allocation of functions and responsibilitie (Selznik in Ndraha, 1997). Considering an organization as a system, components of personnel, purpose, functions and responsibilities constitute to be sub-systems limited by a boundary functioning sequentially to achieve a committed common goal or set of goals (see also Robbins, 1990:4) The School of Public Administration, the National Agency for Public Administration (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara or STIA LAN) is anorganization of functional higher education for civil service, National and Local Corporate employees, and army or police members aiming at improving apparatus competency in the fields of theory and practice of public administration. On the basis of President Decree Number 100 year 1999, STIA constitutes to be a technical operation unit or income-generating unit (Unit Pelaksana Teknis or Lembaga Swadana) under LAN. As a functional school, STIA LAN has specific characteristics both its academic components (curriculum, programs, learning materials, learning techniques and methodology) and structure of organization (components, system and sub-system). As an organization STIA LAN might be considered as a semi-open system. In this context, the components of its system are open for any information concerning the development of public administration from its environment. The information is then processed and modified to be learning materials. However, as a functional institution for apparatus STIA LAN is also closed for external interaction, especially concerning the students and other information related to general higher education. This paper tries to analyze STIA LAN from the spectrum of organization as a system. Through this point of view, some concepts expectedly emerge and develop to be the alternative solution of the recent organization problems.